Furfural and 5-(Hydroxymethyl) furfural Tolerance Candida strains in Bioethanol Fermentation - Ahmad Thontowi; Urip Perwitasari; Lutfi Nia Kholida; Atit Kanti; Yopi; Bambang Prasetya (Annales Bogorienses, 2020)
The toxic fermentation inhibitors in lignocellulosic hydrolysates pose significant problems for the production of second-generation biofuels and biochemicals. Among these inhibitors, 5-(hydroxymethyl)furfural (HMF) and furfural are specifically well known. This study investigated the furfural and 5-HMF tolerance in Candida strains, which could be used for the development of advanced generation bioethanol processes. The 10 isolates of Candida were selected based on the cell growth and bioethanol production on YPD medium containing several concentrations of furfural and 5-HMF by using spectrophotometer and HPLC. Candida parapsilosis Y80 could grow and produce bioethanol in the medium that contains furfural and 5-HMF with a concentration of 60 mM and 40 mM, respectively. Based on the results, C. parapsilosis Y80 has potential activity in the development of bioethanol fermentation.